Studies on yield and biochemical sub-components of latex of rubber trees (Hevea brasiliensis) with a special reference to the impact of low temperature in a non-optimal environment - Alam B; Das G; Dey S K; Pal T K; Roy S; Shammi Raj (Journal of Rubber Research, 2003)
This study was conducted to examine the relationship of yield with latex sub-components with a special reference to low temperature effects in five commercially popular clones (GT 1, RRII 105, RRII 118, PB 235, and RRIM 600) of rubber tree Hevea brasiliensis in a non-traditional area of rubber cultivation in North-East India where low temperature prevails in winter. There was a clear seasonal and clonal variation in yield. The pre-winter (October to November) was the broad peak yielding period. Rubber yield due to low temperature during the winter season (December to February) decreased in the range of about 8;to 40;depending on the clones. Low temperature-induced yield depression was lowest in clone RRIM 600 which indicated its relatively better acclimatisation to the cold climate. Latex thiol content increased about five-fold in the winter season in comparison to the peak yielding pre-winter season. This remarkable increase in thiol content in the latex in the winter season confirmed a positive relation between thiol and cold stress in Hevea for the first time. Sugar and thiol were found negatively correlated with yield. Positive correlations were obtained between yield and maximum temperature (Tmax), minimum temperature (Tmin), the total solid content of latex (TSC) and soil moisture (SM). A multiple regression analysis considering the yield as dependent and sugar, thiol, inorganic phosphate (Pi), TSC, Tmax, Tmin and SM as independent variables revealed that about 41;variability of yield can be explained through these independent variables. Path coefficient analysis proved that thiol, Pi, TSC and SM have major direct effects on yield, while Pi, TSC, Tmin and SM were noted to have direct effects on thiol. Strong relations of thiol with yield and minimum temperature showed that the ratio of yield to thiol would be one of the determinants for rubber producing potential of Hevea clones during winter in the non-optimal environment.
Keywords: Cold stress; Hevea brasiliensis; Inorganic phosphate; Latex; Minimum temperature; Soil moisture; Sugar; Thiol; Yield regulation